Inducible Nitric Oxide Synthase/Nitric Oxide System as a Biomarker for Stress and Ease Response in Fish: Implication on Na+ Homeostasis During Hypoxia - Peter, M. C. Subhash; Gayathry, R.; Peter, Valsa S. (Frontiers in Physiology, 2022)
The cellular and organismal response to stressor-driven stimuli evokes stress response in vertebrates including fishes. Fishes have evolved varied patterns of stress response, including ionosmotic stress response, due to their sensitivity to both intrinsic and extrinsic stimuli. Fishes that experience hypoxia, a detrimental stressor that imposes systemic and cellular stress response, can evoke disturbed ion homeostasis. In addition, like other vertebrates, fishes have also developed mechanisms to recover from the impact of stress by way of shifting stress response into ease response that could reduce the magnitude of stress response with the aid of certain neuroendocrine signals. Nitric oxide (NO) has been identified as a potent molecule that attenuates the impact of ionosmotic stress response in fish, particularly during hypoxia stress. Limited information is, however, available on this important aspect of ion transport physiology that contributes to the mechanistic understanding of survival during environmental challenges. The present review, thus, discusses the role of NO in Na+ homeostasis in fish particularly in stressed conditions. Isoforms of nitric oxide synthase (NOS) are essential for the synthesis and availability of NO at the cellular level. The NOS/NO system, thus, appears as a unique molecular drive that performs both regulatory and integrative mechanisms of control within and across varied fish ionocytes. The activation of the inducible NOS (iNOS)/NO system during hypoxia stress and its action on the dynamics of Na+/K+-ATPase, an active Na+ transporter in fish ionocytes, reveal that the iNOS/NO system controls cellular and systemic Na+ transport in stressed fish. In addition, the higher sensitivity of iNOS to varied physical stressors in fishes and the ability of NO to lower the magnitude of ionosmotic stress in hypoxemic fish clearly put forth NO as an ease-promoting signal molecule in fishes. This further points to the signature role of the iNOS/NO system as a biomarker for stress and ease response in the cycle of adaptive response in fish.